Zeolite Synthesis For Methane Adsorbent: Effect Of Experimental Conditions On Structural Framework Formation - Kamarudin, K. S. N.; Hamdan, H.; Mat, H. (2003)

(untitled)
Zeolites are seen as a potential adsorbent for methane due to the ability of the microporous structure to adsorb molecules selectively, depending upon the size of the pore window. The understanding of factors that affect the formation of zeolite framework is very important as it will affect the physical and chemical properties the zeolite. Therefore, in this research, zeolites have been hydrothermally synthesized in the laboratory with different SiO2/Al2O3, crystallization time, and temperature. SiO2/Al2O3 affects the crystallinity of zeolite sample without changing the structural framework formed. However, crystallization time and temperature affect the structural frameworks formed.